KUALITAS PELAYANAN PEMBUATAN SURAT KETERANGAN KELAHIRAN DI KANTOR DESA SEBARRA KECAMATAN PARINDU KABUPATEN SANGGAU - Marius Ramona Vickson E.42009021 (FISIP Universitas Tanjungpura Pontianak, 2022)
This research aims to find out about the process of the manufactured of Birth Certificate at Sebarra Village. It Process based on indicators of the quality of service, that is Tangiable (service embodiment), Reliability (reliability of officers), Responsiveness (response of officers), Assurance (security services) This research uses a qualitative descriptive approach. Techniques of data collection were interviews and documentation. Location of the study at Sebarra Village Office, Parindu District. Subjects were the head of Sebarra Vilagge, Secretary of Sebarra Village Office, Head of Government affairs Sebarra Village Office and Residents Applicant Making Birth Certificate. The conclution this research is on the makin birth certificate at Sebarra Village Office have poor quality. This is because the lack of excellence services, reliability officer stil low, the lack of responsiveness from the official, and no guaranted on making service of The Birth Certificate. Keywords: Services Process, Making Birth certificate, Quality of services